Mengapa Perusahaan Melakukan Tax Avoidance? Berdasarkan Sudut Pandang Perusahaan Keluarga - Nurul Emil Safitri; Nadya Annisa Nasruddin; Nurkholifah Burhanuddin (Jurnal Akuntansi dan Keuangan, 2025)
This article aims to examine the factors that drive individuals to engage in tax avoidance, particularly within the context of family firms. It adopts a systematic article selection method and a narrative review, applying the four-step PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. Tax avoidance in family firms is shaped by concentrated ownership structures, family involvement in management, and firm size, which collectively create both opportunities and capacities for such practices. The article provides valuable insights for regulators, tax auditors, and other tax authorities in identifying the characteristics and primary determinants of tax avoidance in family firms. In addition, it highlights the schemes and motivations underlying tax avoidance practices in this context.